Evaluasi Kualitas Pelayanan Bank Syariah Indonesia: Studi Empiris Pembayaran UKT di Jambi - Titin Agustin Nengsih; Ahmad Syahrizal; Sellin Fidia Oktafiani (Universitas Batanghari Jambi, 2021)
Customer satisfaction is very important for a company engaged in banking services. To achieve customer satisfaction, it needs to pay attention to several factors, one of which is the quality of service. The purpose of this study is to find out the influence of the quality of service during the tuition fees at Bank Syariah Indonesia on the satisfaction of students of the Faculty of Economics and Islamic Business UIN STS Jambi. The research was conducted by distributing questionnaires to 344 customers who are students of FEBI UIN STS Jambi. Multiple regression analysis results in that all dimensions of service quality significantly affect customer satisfaction. These dimensions are variables of physical evidence, reliability, responsiveness, assurance, and empathy. The five variables were able to explain customer satisfaction by 74,1%.